2000
DOI: 10.2307/2672910
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Consequences of Increased Disclosure

Abstract: , and the Wharton School. Christian Leuz thanks the Wharton School for its generous support during his visi t.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
1,116
2
55

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,235 publications
(1,239 citation statements)
references
References 37 publications
(51 reference statements)
66
1,116
2
55
Order By: Relevance
“…Welker (1995) used analysts' ratings of overall disclosure policy and confirmed that companies with higher ratings (and respectively higher disclosure) have generally lower bid-ask spreads (costs of capital). This is also supported by Leuz and Verrecchia (2000), who considered the switching from the local (German) GAAP to IFRS or US GAAP as a sign for increased voluntary disclosure, and proved that this change decreased the bid-ask spreads for firms on the German market. Cuijpers and Buijink (2005) also confirmed the expected association, but only for firms with high analyst following, while Daske (2006) found no empirical evidence that German firms, adopting higher disclosure standards, reduce their cost of equity financing.…”
Section: Empirical Literaturementioning
confidence: 73%
See 1 more Smart Citation
“…Welker (1995) used analysts' ratings of overall disclosure policy and confirmed that companies with higher ratings (and respectively higher disclosure) have generally lower bid-ask spreads (costs of capital). This is also supported by Leuz and Verrecchia (2000), who considered the switching from the local (German) GAAP to IFRS or US GAAP as a sign for increased voluntary disclosure, and proved that this change decreased the bid-ask spreads for firms on the German market. Cuijpers and Buijink (2005) also confirmed the expected association, but only for firms with high analyst following, while Daske (2006) found no empirical evidence that German firms, adopting higher disclosure standards, reduce their cost of equity financing.…”
Section: Empirical Literaturementioning
confidence: 73%
“…Hail (2002) argues that the number of analysts is not that influential on the cost of equity capital and both firms with high and low analyst following can reduce their cost of equity financing by increasing the level of disclosure. In line with Healy et al (1999) and Leuz & Verrecchia (2000), he suggests that concentrating on specific occasions and reporting environments, where one can observe significant changes in firms' disclosure actions, makes the subtle effect of voluntary disclosure more easily detectable.…”
Section: Introductionmentioning
confidence: 97%
“…Using the spread to control a firm's informational environment, Healy and Palepu (1995) and Welker (1995) found a negative (positive) relationship between spread and the quality of information disclosure (information asymmetry). Healy et al (1999) and Leuz and Verrecchia (2000) showed that information asymmetry, the spread, and volatility of stock prices are negatively associated with quality disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the determinants of audit fee are corporate size (Waresul & Moizer, 1996;Sandra & Patrick, 1993;Kamal & Rana, 2008), status of the audit firm (big 4 or non-big 4) (Waresul & Moizer, 1996;Kamal & Rana, 2008), industry type (Mohd & Takiah, 1993;Kamal & Rana, 2008;Leventis, Hassan & Dedoulis, 2013;Casterella, Desir & Irwin, 2013), degree of corporate complexity (Sandra & Patrick, 1993;Kamal & Rana, 2008;Sundgren & Svanstrom, 2013), perceived risk (Sandra & Patrick, 1993;Mark et al, 2007;Kamal & Rana, 2008;Aswadi et al, 2009;Kim & Fukukawa, 2012), ownership concentration (Aswadi et al, 2009), type of equity ownership (Badertscher et al, 2013) and audit delay (Sandra & Patrick, 1993;Coster, Dahl & Jenson, 2013). In addition, Taylor & Simon (1999) found that higher audit fee is associated to litigation propensity, higher level of disclosure (and stringent regulation while Stanley (2011) finds that audit fees reflects future changes in client earnings.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The selection of control variables in model was mainly based on the extensive past literature such of Waresul & Moizer (1996), Sandra & Patrick (1993), Kamal & Rana (2008), Mark et al (2007) and also an adaptation from the study of Lin & Liu (2009).…”
Section: H1mentioning
confidence: 99%